Abundance of Chaetodontidae Family Reef Fish and Coral Reef Condition in the Sikuai Island Area, West Sumatra - Yosefa, Bella; Thamrin, Thamrin; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2025)
Coral reefs are massive piles of sediment from calcium carbonate produced by the phylum cnidaria, class Anthozoa, and order Madreporaria, with the addition of calcareous algae and other organisms that produce calcium carbonate. One group of biota that lives in association with coral reefs and plays a vital role in the coral reef ecosystem is the Chaetodontidae fish. The taking of the Chaetodontidae family as research material is because the coral fish of the Chaetodontidae family are indicator fish for coral reef health that can assess, monitor and predict the condition of coral reefs. Given the importance of the function and the existence of coral reefs. This study aimed to determine the condition of coral reef cover, analyze the abundance of reef fish in the Chaetodotidae family, and determine the relationship between coral reef cover and the abundance of reef fish in the Chaetodotidae family. This study was conducted in December 2024 in Sikuai Island, West Sumatra. This study used survey methods, such as UVC (underwater visual census) and UPT (underwater photo transect). The research location was divided into three stations in the southern part of Sikuai Island because the southern part is relatively protected from large waves during the west wind season. Station I is next to Sirandah Island, Station II is in the harbour area, and Station III is in the abandoned ship area. The analysis showed that the highest percentage of coral cover was found at Station III, namely 45.13%, and the lowest rate was found at Station I, 6.47%. The calculation of reef fish abundance showed that the highest abundance of reef fish was found at station III, namely 5000 ind / ha and the abundance of reef fish at station I was 6.47%.